2021
DOI: 10.1002/jeq2.20267
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of polycyclic aromatic hydrocarbons in the devitalized aquatic moss Fontinalis antipyretica: From laboratory to field conditions

Abstract: This work aims to test the feasibility of a Fontinalis antipyretica devitalized moss clone to uptake and accumulate polycyclic aromatic hydrocarbons (PAHs) from surface waters. To assess the capability of the devitalized clone to accumulate PAHs, in the laboratory, moss was placed in water and spiked with increasing concentrations of 16 PAHs, and under field conditions, the moss was transplanted to 22 sites of Galicia (Spain) rivers. In general, PAH concentrations in water samples were lower than the maximum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In the context of the analysis of the results and their discussion, it is also essential to emphasize the influence of moss biology on their accumulation of analytes (Świsłowski et al 2021d ). Many studies postulate the use of devitalized material, which is an effective monitor of contamination and has many advantages, according to the literature (Carrieri et al 2021 ; Vázquez-Arias et al 2024 ). However, it is essential to remember that the bioindicator is a living organism, not only a chemical sorbent (Boquete et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of the analysis of the results and their discussion, it is also essential to emphasize the influence of moss biology on their accumulation of analytes (Świsłowski et al 2021d ). Many studies postulate the use of devitalized material, which is an effective monitor of contamination and has many advantages, according to the literature (Carrieri et al 2021 ; Vázquez-Arias et al 2024 ). However, it is essential to remember that the bioindicator is a living organism, not only a chemical sorbent (Boquete et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…An alternative to classical methods (passive samplers, mobile monitors) (Abad et al 2022 ) is the use of indicator organisms (biomonitors), which prove to be sensitive species to absorbed PAHs (Sulistiyorini et al 2022 ). Mosses are quite commonly used in biomonitoring (Carrieri et al 2021 ; Jovan et al 2021 ). They are used both as passive and active PAH samplers in open areas or in confined spaces (Vuković et al 2014 ; Jayalath et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the vitality aspect is considered in a small number of papers [40,41], although the relevance of considering this parameter in biomonitoring and physiological studies has been demonstrated [42,43]. Nevertheless, a considerable number of studies use devitalized material [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic vegetation (e.g. bryophytes, including mosses) is widely used in research involving active and/ or passive biomonitoring of trace elements (heavy metals and metalloids) and organic compounds [13][14][15]. In addition to their usefulness as biomonitors, mosses are of interest as primary producers that substantially contribute to the energy balance of ecosystems [16], as well as to other ecosystem functions.…”
Section: Introductionmentioning
confidence: 99%